PROGRAM KREATIVITAS MAHASISWA: PENERAPAN METODE VAKT UNTUK BELAJAR SISWA MEMBACA RENDAH DI SDN 35 CAKRANEGARA - Susilawati, Ema Nurdiana; Suryani , Baiq Varida; Lusmayanti, Baiq Sulislia; Azzahra , Kenesya Latifa; Lola, Nurmayanti (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Children with intellectual disabilities are those who experience challenges in intelligence, which impact academic areas such as initial reading. There are several obstacles faced by students, such as difficulty recognizing letters, spelling, and understanding reading material. Therefore, this community service project aims to address the problem of reading ability delay in second-grade students at SDN 35 Cakranegara, which is a serious challenge in basic education. Thus, in the learning process, implementing the appropriate VAKT (Visual, Auditory, Kinesthetic, Tactile) method can help reduce the barriers experienced by intellectually disabled children, while also involving parents in the learning process at home. The positive results that have been achieved and the potential to significantly improve students' reading abilities. Various outcomes, such as increased interest in reading, development of literacy skills, and ongoing evaluation, indicate that a multisensory approach can be an effective solution in addressing educational challenges in schools. Keywords: academic, elementary school students, beginner reading, VAKT method.